Feature Selection in High Dimensional Biomedical Data Based on BF-SFLA - Dai, Yongqiang; Niu, Lili; Wei, Linjing; Tang, Jie (Frontiers in Neuroscience, 2022)
High dimensional biomedical data contained many irrelevant or weakly correlated features, which affected the efficiency of disease diagnosis. This paper presented a feature selection method for high dimensional biomedical data based on the chemotaxis foraging-shuffled frog leaping algorithm (BF-SFLA). The performance of the BF-SFLA-based feature selection method was further improved by introducing chemokines operation and balanced grouping strategies into the shuffled frog leaping algorithm, which maintained the balance between global optimization and local optimization and reduced the possibility of the algorithm falling into local optimization.To evaluate the proposed method’s effectiveness, we employed the K-NN (k-nearest Neighbor) and C4.5 decision tree classification algorithm with a comparative analysis. We compared our proposed approach with improved genetic algorithms, particle swarm optimization, and the basic shuffled frog leaping algorithm. Experimental results showed that the feature selection method based on BF-SFLA obtained a better feature subset, improved classification accuracy and shortened classification time.